From Framework to Practice: Person‐Directed Planning in the Real World. Issue 6 (8th September 2015) - Martin, Lynn; Grandia, Philip; Ouellette‐Kuntz, Hélène; Cobigo, Virginie
Abstract : Background: Person‐directed planning (PDP) is an approach to planning supports that aims to redistribute power from the service system to individuals with intellectual and developmental disabilities (IDD) and natural supports, improve relationships and build community. To do this, the right people with the right attitudes engaging in the right actions are needed. This paper examines how key elements in PDP contribute to successes in planning. Materials/Methods: Researchers worked with three planning teams from different community service agencies using participatory action research techniques (i.e. free list and pile sort, Socratic wheel, whys/hows exercise). Results: Most key elements of PDP were relevant to each team. Perceptions of which had most contributed to planning successes differed. Conclusions: The various elements of PDP are used by and useful to planning teams, although some may be more relevant to some successes than others because of specific goals, or the person's strengths and needs.